Technical education performance inspection (II): interviews - José Francisco Pérez Aguilar (ADIDE Federación, 2014)
Education inspectors interview technique applied in conjunction with the observation, prior or subsequent to this, allowing triangulate the information obtained to visit the classroom or continue with the collection of evidence. The interview requires the inspector planning a number of aspects to these expected results are obtained and becomes an opportunity to continue to seek or contrasting information available. Also, this technique is a good way to develop the advisory role for inspectors use the interview to return information about the observed along with recommendations, proposals or requirements, if any. But the performance of the educational inspection is not limited to the interview but also meets and calls commissions, boards and tribunals where, besides the above, develop the rest of its functions and powers. This article addressed on the one hand, interviews, and other meetings, commissions, boards and tribunals. In each of the two sections most relevant aspects were addressed and that are directly related to the educational inspection, special importance which are imported from the qualitative or ethnographic research since, with nuances usually applied by education inspectors.